Hubungan Tingkat Kecemasan Dengan Koping Keluarga Pada Pasien Cedera Kepala Di Ruang Icu Rsi Surakarta - PRASETYO WIBOWO, DHODO; , Agus Sudaryanto, S. Kep, Ns, M. Kes; , Faizah Betty R.A., S.Kep., M.Kes (2017)
Anxiety is an uncomfortable feeling / vague worries that accompanied the response autonomy (resources are often not specific or unknown to the people). Feelings of fear caused by the anticipation of danger. This is a sign of vigilance warn people of the dangers and enables individuals to act in the face of threats. Koping is a cognitive and behavioral efforts are being made to regulate certain external and internal relations which limit the resources of a person. Coping can be adaptive (effective) and maladaptive (ineffective). The purpose of this study is the relationship anxiety with coping Knowing the family in cases of head injury in the ICU RSI Surakarta. This research method using non-experimental research with a quantitative approach to the design of descriptive correlative study design used is cross sectional. The sample in this study amounted to 44 respondents. Data analysis with Kendall tau test, which aims to determine the relationship between the level of anxiety of families with coping mechanisms used by the family, assuming ordinal and nominal research. Based on the results of the test analyst Kendall tau correlation r = -0539 values obtained with p = 0.001. p value <0.05 indicates that H0 is rejected it means there is a relationship between anxiety with family coping in cases of head injury in the ICU RSI Surakarta.